Resolution to Ethnic Conflict: Anti-Chinese Riots in Garut, Indonesia, in the middle of the Twentieth Century - Hidayat, Asep Achmad (TEMALI : Jurnal Pembangunan Sosial, 2024)
The Anti-Chinese riots in Indonesia are a dark side of history that must be uncovered. The riots caused by ethnicity and racism worldwide, such as the recent Anti-Chinese issue in the United States, also occurred even in Indonesia after World War II. The racial riots in Garut destroyed Chinese-owned houses, factories, and shops on two consecutive days. The research uses historical methods, namely heuristics, criticism, interpretation, and historiography, that reveal the memories of victims, perpetrators, witnesses, and rare primary personal archives. Through a social history approach, the research indicates that not only ethnicity causes violence but also social, political, and religious sentiments initiated by youth organizations, local religious leaders, and former followers of the revolutionary movement. This study provides benefits so that the public and stakeholders can manage ethnic, religious, racial, and inter-group issues to avoid ethnic conflicts that end in violence.